2(2x+3)3(5x+4)=

Simple and best practice solution for 2(2x+3)3(5x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+3)3(5x+4)= equation:


Simplifying
2(2x + 3) * 3(5x + 4) = 0

Reorder the terms:
2(3 + 2x) * 3(5x + 4) = 0

Reorder the terms:
2(3 + 2x) * 3(4 + 5x) = 0

Reorder the terms for easier multiplication:
2 * 3(3 + 2x)(4 + 5x) = 0

Multiply 2 * 3
6(3 + 2x)(4 + 5x) = 0

Multiply (3 + 2x) * (4 + 5x)
6(3(4 + 5x) + 2x * (4 + 5x)) = 0
6((4 * 3 + 5x * 3) + 2x * (4 + 5x)) = 0
6((12 + 15x) + 2x * (4 + 5x)) = 0
6(12 + 15x + (4 * 2x + 5x * 2x)) = 0
6(12 + 15x + (8x + 10x2)) = 0

Combine like terms: 15x + 8x = 23x
6(12 + 23x + 10x2) = 0
(12 * 6 + 23x * 6 + 10x2 * 6) = 0
(72 + 138x + 60x2) = 0

Solving
72 + 138x + 60x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '6'.
6(12 + 23x + 10x2) = 0

Factor a trinomial.
6((3 + 2x)(4 + 5x)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5

Subproblem 2

Set the factor '(4 + 5x)' equal to zero and attempt to solve: Simplifying 4 + 5x = 0 Solving 4 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5x = 0 + -4 5x = 0 + -4 Combine like terms: 0 + -4 = -4 5x = -4 Divide each side by '5'. x = -0.8 Simplifying x = -0.8

Solution

x = {-1.5, -0.8}

See similar equations:

| (0.25*X)+X=3665.00 | | 6-2z=18-3z | | -3/4w=15 | | f*4+5=11 | | .25x=1567.50 | | (a+3)(a+3)=0 | | 3cos^2(x)-5cos(x)=2 | | -u/u^2 | | x-7(2x-3)=2(5x-2)-3(4x+9) | | (36y^2)-5=y-18y^2 | | -2+3(x-4)=3x-9(x-3)-1 | | 7(x-8)+9=5(x-7) | | 4x-2y=800 | | 5x+3-1*2=54 | | 7(x+6)+x=4(4x+4)+6 | | 2a+7=25+8 | | .417/.875 | | 3x-2(3x-2)=6-(3x-8)+9x | | 7(x-3)+x=2(x+5)+2 | | X^2+x-2=x^3 | | 5/12/7/8 | | (-4+7i)(1+i)= | | 4(2x+5)-(8x+5)=15 | | (3x^4)/(6)=x^6/30 | | 12x/15x | | -(6-3*6)-5=-2*6-2*6+1solve | | X^7=x^4+65 | | .2(4z-10)=.8z-2 | | 1/5(4z-10=4/5z-2 | | (2-v)(2v-3)=0 | | -4(x-4)+5=6(x+4)+1 | | 2x+2X+x=940 |

Equations solver categories